Investigation into the dynamic change pattern of the stress field during integral fracturing in deep reservoirs - Lv, Bei; Lv, Zhenhu; Luo, Yao; Chen, Jiameng; Zhang, Li; Wang, Bo (Frontiers in Energy Research, 2023)
Deep reservoirs have high temperature, high pressure, and high stress. The development of such resources is high cost. Integral fracturing applies one-time well displacement, batch drilling, and batch fracturing. Multiple wells are stimulated with zipper fracturing. It can avoid the interference of the well drilling and fracturing. In this way, the spatial stresses can be utilized to generate the complex fracture network. The dynamic change pattern of the stress field is of great value for the design of integral fracturing. Based on the displacement discontinuity method (DDM) and the fracture mechanics criteria, a whole fracture propagation program is developed to calculate the spatial stress distribution and the whole fracture geometry. The reliability of the program is verified against the classical analytical solutions. Based on the program, this work systematically investigates the effects of the fracture length, the fracturing sequence, the fracture distribution mode, and the injection pressure on the stress field. The main conclusions are as follows: 1) When the fracture half-length is 150 m and the well spacing is 300 m, the staggered fracture distribution mode can ensure uniform fracture propagation and realize the active utilization of inter-well stress field; 2) Compared with the relative fracture distribution mode, the staggered fracture distribution mode is less susceptible to the stress field induced by the adjacent hydraulic fractures, hydraulic fractures tend to propagate along the direction of the maximum horizontal principal stress; 3) The stress field is highly influenced by the in-fracture fluid pressure. The stress interference is stronger with a greater fluid injection pressure and a higher fracture deflection angle will be obtained. It can enhance the fracture propagation resistance and increase the stress value. This work discovers the stress change pattern and lays out a solid foundation for the optimization of the integral fracturing.